Analyzing Real-Time Application Logs for Informed Decision Making - Ramasankar Molleti (International Journal of Intelligent Systems and Applications in Engineering, 2021)
This technical report explains how the key control of real-time application log analysis has been dismantled in present day software development and activities. It looks at the definition, types, and importance of the real-time log and the tools and techniques for driving the analysis. Looking at the benefits and challenges of real-time log analysis, the report also provides recommendations for implementation and use cases as well as the best practices of using log data for decision-making processes. As real-life examples demonstrate, real-time log analysis can also foster application execution, update security, and redesign clients’ experience according to this report. DOI: https://doi.org/10.17762/ijisae.v9i1.6712